Resilience and Solidarity of the Kemiri Village Community After Natural Disasters from a Sociological Perspective - Muhammad Albar Haudan; Syahrizal Bayu Almeida; Mukhammad Handy Wijaya; Dodik Harndi; Joko Mulyono (Jurnal Masyarakat Maritim, 2025)
This study examines the resilience and solidarity of the Kemiri Village community in the aftermath of natural disasters, viewed through a sociological lens. The research seeks to understand how social structures, collective values, and cultural mechanisms have shaped community responses to crisis situations, particularly in rebuilding livelihoods and restoring social cohesion. Using a qualitative descriptive method, data were gathered through in-depth interviews, participatory observation, and documentation involving community leaders, disaster survivors, and local institutions. The analysis draws upon theories of social resilience and collective solidarity to interpret patterns of adaptation, cooperation, and mutual aid among residents. The findings reveal that community resilience in Kemiri Village is deeply rooted in traditional social networks, kinship systems, and religious values that encourage mutual support and collective problem-solving. Social capital plays a pivotal role in mobilizing resources, rebuilding infrastructure, and ensuring the equitable distribution of aid. Furthermore, local leadership and informal institutions such as community prayer groups and neighborhood associations acted as mediating agents that strengthened coordination between residents and external relief organizations. Solidarity was expressed through “gotong royong” (mutual cooperation), communal labor, and emotional support, which helped alleviate psychological trauma and fostered a sense of belonging. The study concludes that resilience in Kemiri Village is not merely a product of material recovery but also of cultural endurance and moral unity. Strengthening participatory governance, promoting inclusive disaster education, and preserving traditional values of solidarity are essential to enhancing long-term resilience in rural communities facing recurring natural hazards.